Checkpoint inhibitors in pancreatic cancer. (August 2019) - Henriksen, Andreas; Dyhl-Polk, Anne; Chen, Inna; Nielsen, Dorte
Highlights: Activity was not demonstrated with single-agent checkpoint inhibitors. Combination therapy showed promise. Overall, markedly response was not shown. Abstract: Introduction: Immune checkpoint inhibitors, targeting cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and the programmed cell death protein-1 (PD-1)/programmed cell death ligand-1 (PD-L1) pathways have shown remarkable potential in several types of cancer. In this review we summarize published and ongoing studies on checkpoint inhibitors in pancreatic cancer (PC). Methods: We conducted a systematic literature search using Medline and Embase up to November 2018; additional data from a search on clinicaltrials.gov were included. Endpoints of interest encompassed overall survival (OS), progression free survival (PFS) and response rates. Results: Full-length articles constituted a minority of included records. Furthermore, few patients were enrolled, and only few phase II studies were identified. Disappointing limited activity was demonstrated with single-agent checkpoint inhibitors in PC. A small number of studies on combination therapy showed promise with regards to response. But overall, PC patients treated with checkpoint inhibitors were not shown to elicit improvement in response rates or overall survival. Conclusion: Checkpoint inhibition monotherapy has failed to elicit efficacy in patients with pancreatic cancer. Combination regimens including chemotherapy have shown initial promise, but these results need to be verified. Numerous studies on checkpoint inhibition in PC are ongoing.